Perbandingan Hasil Belajar Siswa Pada Pembelajaran Matematika Melalui Pemanfaatan Media Gambar Dan Media Konkret Di Kelas V SDN 52 Kota Bengkulu - Nigtyas Ningtyas; Ansyori Gunawan; Daimun Hambali (JURIDIKDAS, 2018)
This study aims to compare learning outcomes through image media and concrete media, and to find out which instructional media is more effective for use in learning mathematics class V SDN 52 Bengkulu. This research is a quantitative research. The research design used was quasi experimental research. Type of Research Design is the Pretest-Posttest Matching Comparison Group Design. In this design two tests were conducted, before and time to provide treatment  in the experimental class. The population in this research is the students of class V SDN 52 Bengkulu city. Sampling technique using purposive sampling. The sample selected is the VA class as the experimental class 1, and the VC class as the experimental class 2. The data completion instrument used is a short test provided through the pretest (Before the learning took place) and posttest (after the learning took place). Data of this research are analyzed using inferential statistic that is t-test. From result of research result of t test equal to 1,73> t table equal to 1,67 at significant level 5%. So it can be concluded that there is a significant difference in the learning outcomes of students of grade V SDN 52 Bengkulu on learning mathematics between students who use the images media with students who use concrete media.